Advancing Islamic Financial Planning in Indonesia: Principles, Challenges, and The Role of Tawhid String Relationship Theory - Diani, Treska Melsa; Nugroho, Lucky (Economics & Islamic Finance Journal (ECIF), 2024)
The rapid development of Islamic or Sharia financial planning in Indonesia reflects the country’s demographic strength as the largest Muslim-majority nation. Rooted in Sharia principles, Islamic financial planning emphasizes the prohibition of riba, gharar, and maysir, integrating ethical wealth management, risk-sharing, and social responsibility through mechanisms like zakat, waqf, and sadaqah. Despite a significant increase in Islamic financial literacy, challenges persist, including limited accessibility in rural areas and low public understanding of Islamic financial concepts. This study aims to identify the basic principles and concepts of Islamic financial planning, highlight the urgency of its implementation, and examine its practical application in Indonesia. Using a descriptive qualitative approach and literature review, the research draws on secondary data from Qur’anic texts, Hadith, academic journals, and regulatory reports from institutions like OJK and Bank Indonesia. The findings emphasize the pivotal role of the Tawhid String Relationship (TSR) theory in aligning financial practices with spiritual and societal obligations. TSR provides a comprehensive framework for ethical and sustainable financial management, connecting human relationships with Allah (habluminallah) and society (habluminannas). The study concludes that Islamic financial planning in Indonesia offers substantial opportunities for growth through fintech innovations and regulatory support. Its implementation can foster inclusive economic development, strengthen social welfare, and position Indonesia as a global leader in Islamic finance. The study provides theoretical insights and practical implications for advancing Islamic financial systems in both national and global contexts.